PECULIARITIES OF INTERACTION BETWEEN CITELLOPHILUS TESQUORUM ALTAICUS (IOFF, 1936) FLEA AND YERSINIA PESTIS WITH VARIOUS PLASMID COMPOSITION - L. P. Bazanova; E. G. Tokmakova; G. A. Voronova; S. V. Balakhonov; T. I. Innokent’eva (Проблемы особо опасных инфекций, 2017)
Objective of the study is in vitro investigation of mutual relations between Citellophilus tesquorum altaicus and Yersinia pestis with various plasmid composition: influence of the strain on flea alimentary activity and mortality rate, frequency and dynamics of biofilm formation.Materials and methods. C. tesquorum altaicus were infected by three Yersinia pestis strains: virulent triple-plasmid I-3230 isolated in Mongolia, referential for the Tuva focus I-2638 carrying four plasmids (pYT, pYV, pYP, pTP 33) and also selected from it avirulent isogenic clone I-3480 that lost two plasmids (pYV, pYP). Peculiarities of interaction between fleas and Y. pestis strains were estimated through the lens of specimens with «conglomerates» and “blocks” for feeding, the period from infection prior to the beginning of conglomerates’ formation, alimentary activity, and mortality rate of the infected fleas.Results and conclusions. It was revealed that alimentary activity of the infected insects was higher than that of the control group, and the highest – in fleas infected with I-2638 strain. Greater numbers of dead fleas at feeding was noted in specimens inoculated with I-3230 strain. Predominant significance of I-2638 strain was established in C. tesquorum altaicus biofilm formation both as «conglomerates» and “blocks”. I-3480 strain also formed the conglomerates in fleas more actively than I-3230 lacking pTP33 plasmid. Thus, four-plasmid I-2638 strain surpassed triple-plasmid I-3230 and two-plasmid I-3480 strains in reference to all tested indicators except flea mortality rates. It may testify to co-adaptation of Y. pestis and C. tesquorum altaicus from the Tuva plague focus and to the possibility of a pTP33 functional role in enhancement of a biofilm formation in vivo.